2017
DOI: 10.1108/ilt-04-2017-0098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface roughness and deformation on Rayleigh step bearing under thin film lubrication

Abstract: Purpose The aim of this paper is to study the effect of deterministic roughness and small elastic deformation of surface on flow rates, load capacity and coefficient of friction in Rayleigh step bearing under thin film lubrication. Design/methodology/approach Reynolds equation, pressure-density relationship, pressure-viscosity relationship and film thickness equation are discretized using finite difference method. Progressive mesh densification (PMD) method is applied to solve the related equations iterative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…Figure 8 showcases the non-dimensional load carrying capacity at different values of film thickness ratio with varying minimum film thickness. Under the EHL condition (as shown in Figure 8(a); Kumar et al 24 ), the load carrying capacity is slightly greater compared to that in the Thermo-EHL condition (as shown in Figure 8(b)) for all values of minimum film thickness. This is because the position of maximum pressure and the area under the no-pressure zone are affected by the generated temperature, as it tends to reduce the generated pressure and no-pressure zone (as discussed in Section 3.2) and finally the load carrying capacity.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Figure 8 showcases the non-dimensional load carrying capacity at different values of film thickness ratio with varying minimum film thickness. Under the EHL condition (as shown in Figure 8(a); Kumar et al 24 ), the load carrying capacity is slightly greater compared to that in the Thermo-EHL condition (as shown in Figure 8(b)) for all values of minimum film thickness. This is because the position of maximum pressure and the area under the no-pressure zone are affected by the generated temperature, as it tends to reduce the generated pressure and no-pressure zone (as discussed in Section 3.2) and finally the load carrying capacity.…”
Section: Resultsmentioning
confidence: 89%
“…Figure 10 shows the non-dimensional coefficient of friction for the EHL condition (as shown in Figure 10(a); Kumar et al 24 ) and the Thermo-EHL (as shown in Figure 10(b)) condition at different film thickness ratios. In both conditions the frictional coefficient is more for h 2 = 200 nm at a small value of k .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Reynolds equation is confined to just the contact region, but the Navier-Stokes equations can be applied throughout the flow field [24,25]. In order to optimize Rayleigh step bearing design scientifically, it is beneficial to obtain detailed flow information of the whole lubricant flow field [26].…”
Section: Introductionmentioning
confidence: 99%